2019
DOI: 10.1186/s40168-019-0746-y
|View full text |Cite
|
Sign up to set email alerts
|

Commensal-derived metabolites govern Vibrio cholerae pathogenesis in host intestine

Abstract: Background Recent evidence suggests that the commensal microbes act as a barrier against invading pathogens and enteric infections are the consequences of multi-layered interactions among commensals, pathogens, and the host intestinal tissue. However, it remains unclear how perturbations of the gut microbiota compromise host infection resistance, especially through changes at species and metabolite levels. Results Here, we illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 75 publications
3
53
0
Order By: Relevance
“…This finding is consistent with experiments of SCFAs applied to animal models. B. vulgatus has been shown to inhibit V. cholerae colonization in mice, an effect that was dependent upon SCFAs butyrate and propionate production (13). SCFAs are known to impact immune cell development and attenuate inflammation by inhibiting histone deacetylases and other mechanisms of altering gene expression (2629).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with experiments of SCFAs applied to animal models. B. vulgatus has been shown to inhibit V. cholerae colonization in mice, an effect that was dependent upon SCFAs butyrate and propionate production (13). SCFAs are known to impact immune cell development and attenuate inflammation by inhibiting histone deacetylases and other mechanisms of altering gene expression (2629).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a species enriched in the gut microbiota of patients recovering from cholera, Blautia obeum , was found to interfere with V. cholerae pathogenicity through quorum-sensing inhibition in a mouse model (8). Animal and in vitro experiments have demonstrated that alteration of commensal-derived metabolite levels influenced host susceptibility by affecting V. cholerae growth or colonization (913).…”
Section: Introductionmentioning
confidence: 99%
“…An important caveat underlying our findings is that GF mice lack commensal gut microbes and could have altered immune responses to immunization, especially considering recent studies that have highlighted how V. cholerae-microbiota interactions can influence colonization, disease, and development of anti-V. cholerae immunity [48][49][50][51][52] . However, the strong association of VAT induction with protection and superior efficacy of live over inactivated vaccine strains in this model, and our similar findings of OCV function in mice with transiently disrupted microbiomes reinforces the idea that the GF mouse live OCV model holds substantial translational promise 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…As the treatment progresses, the abundance of Bifidobacterium and SCFAs were return to normal levels (Monira et al, 2010). Besides, mice treated with clindamycin reduced the abundance of Bacteroides and the content of SCFAs to enhance the colonization ability of V. cholerae (You et al, 2019). All these indicate that probiotics in the host can antagonize the colonization of V. cholerae by secreting SCFAs.…”
Section: Bioactive Metabolites-depended Crosstalk Between Gut Microbimentioning
confidence: 92%